Exploring Genetic Variability and Cause-effect Relationship for Yield and its Contributing Traits in Brinjal (Solanum melongena L.) - Teja, Bannaravuri Lalithya; Sadhu, Supratim; Hijam, Lakshmi; Roy, Suvendu Kumar; Chatterjee, Ranjit; Chakraborty, Moumita (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted with sixteen distinct brinjal (Solanum melongena L.) genotypes during October, 2018 to February, 2019 at Horticultural Research cum Instructional farm under All India Coordinated Research Project (AICRP) on vegetable crops at Uttar Banga Krishi Viswavidyalaya, Pundibari of Cooch Behar district in West Bengal (736 165), following randomized block design to analyze genetic variability, correlation, and path coefficients to identify traits influencing fruit yield. Significant genetic variability among all traits indicated ample scope for effective selection in the breeding programme. High heritability (>60%) coupled with substantial genetic advance (>20%) found for traits like fruit yield, fruit weight, and fruits plant-1 suggested the presence of strong additive gene action, which favoured direct selection. Correlation analysis identified positive associations of fruit yield with the number of branches plant-1, fruits plant-1, and fruit weight, while infested branches plant-1 negatively impacted yield. Path analysis revealed fruits plant-1 (0.606) and the number of branches plant-1 (0.564) had the highest direct effects on fruit yield, supported by strong positive correlations. Other traits like fruit diameter (0.545), days to 50% flowering (0.370), fruit weight (0.200), and phenol content (0.194) contributed positively. Negative direct effects of fruit length, fruit girth, and days to maturity indicated limited influence on fruit yield. A low residual effect (0.0463) validated the adequacy of selected traits in capturing genetic variability. The study emphasized the number of branches plant-1 and fruits plant-1 were critical traits for yield improvement, providing a robust framework for developing high-yielding, brinjal genotypes for sustainable cultivation.